RANCANG BANGUN SISTEM PEMESANAN CATERING DAN DEKORASI DI SUMBAWA BESAR BERBASIS ANDROID - Rodianto Rodianto; Arni Safitri (Sekolah Tinggi Teknik - PLN, 2018)
The catering and decorating process in Sumbawa is still conventional. So that the service procedure which applied for now are still less effective and efficient. This process incude to the owners of catering and decoration that could does a mistake, among others, the double order, the order making was not in order due to the accumulation of order notes, especially when crowded customers ordered by telephone or short message which could occur human error such as forgetting the order customer, and pen or order paper that runs out. The software is built by using the programming languages PHP, MySQL, Java and Android Studio. The purpose of making this ordering system is to help the owner of catering nusiness and decoration in Sumbawa besar to improving the quality of their business in the eyes of customers. This ordering system has a service that makes customers know the that location of the place of residence of the business owner as to minimize the occurrence of customer concers for message that are not served. The method used is a method of data collection and software development. The software development process model is used in the waterfall model which consist (1) analysis, (2) design, (3) coding, (4) program testing, (5) maintance.